Do more masculine-faced CEOs reflect more tax avoidance? Evidence from Indonesia - Iman Harymawan; Nadia Anridho; Adib Minanurohman; Sri Ningsih; Khairul Anuar Kamarudin; Yulianti Raharjo (Cogent Business & Management, 2023)
The present paper provides new empirical evidence on the relationship between CEO facial masculinity and tax avoidance. We use data from non-financial companies listed on the Indonesia Stock Exchange during the period 2010-2019. The findings suggest that the CEO facial masculinity is positively associated with tax avoidance, which is one of the risky financial decisions. We also conducted a battery of robustness tests, including testing the sample of companies with/without a risk management committee, the interaction with CEO age and big 4 audit firm, the implementation of the tax amnesty in Indonesia, and addressing endogeneity using the propensity score matching. The current measurement of CEO masculinity, which is based on the fWHR of the CEO's photo, could be further developed by future studies using artificial intelligence (AI) technology. This study contributes to the literature on CEO characteristics by filling in the gaps of biological characteristics associated with tax avoidance decisions. This is the first study investigating the relationship between CEO biological characteristics and tax avoidance.
Keywords: 650; governance; tax avoidance; -masculinity; CEO